The leadership pipeline : how to build the leadership-powered company - Charan, Ram; Drotter, Stephen;Noel, James (San Francisco, California : Jossey-Bass Inc., Publishers, 2011)
An updated and revised version of the bestselling The Leadership Pipeline - the critical resource for how companies can grow leaders from the inside. In business, leadership at every level is a requisite for company survival. Yet the leadership pipeline -the internal strategy to grow leaders - in many companies is dry or nonexistent. Drawing on their experiences at many Fortune 500 companies, the authors show how organizations can develop leadership at every level by identifying future leaders, assessing their corporate confidence, planning their development, and measuring their results. New to this edition is 65 pages of new material to update the model, share new stories and add new advice based on the ten more years of experience.
Six leadership passages : an overview -- From managing self to managing others -- From managing other to managing managers -- From managing managers to functional manager -- From functional manager to business manager -- From business manager to enterprise manager -- Diagnostic : identifying pipeline problems an possibilities -- Performance improvement : clarifying roles and creating performance standards -- Succession planning -- Identifying potential pipeline failures -- The functional career passage -- Coaching -- Benefits up and down the line
Includes index.
Keywords: LEADERSHIP